A posse-trabalho - Toledo, Roberta Cristina Paganini (2006)
A work that establishes a comparison between diverse doctrinal, national and foreign positions, in relation to the ownership-work was developed as instrument of accomplishment of the social function of the ownership and the property. The ownership-work is studied under the prism of the real properties. The work will be started with a study, which does not have the pretension to deplete the analysis of this institute. It is presented, to follow, a description not very deepened on the evolution of the legal notion of the possession, that if it initiates with the exposition of the main criteria of the roman chain, passing to that more determinative of the classic theories of Frederich Karl von Savigny and Rudolf von Ihering, proceeding itself in the same way with regard to the social theories of Silvio Perozzi, Francesco Carnelutti, Raymond Saleilles and Antonio Hernandez Gil, who much had influenced the legal world contemporary. The ownership-work passes to be examined under the optics of its repercussion in relation to the stated periods, establishing itself a comparison enters those established for it in such a way and those determining for the acquisition of the property through the processory title as of the surface right. The social functions of the property and the possession will be visited of the point of view of its constitutionality, and also its consequences on Civil Code and the Statute of the City. In the comparative jurisprudence, similarities will be searched and differences of the analyzed justinian codes, with a special approach, are clearly, in the institute ownership-work and its effect, for being it it object of the present work. Finally, study on the right will be carried through, under the optics of the intertemporary and the rules of transistion established by this new civil statute in such a way for the figures of the usual and extraordinary processory title, as for the judicial dispossession, in which the qualified ownership for the work has place